PELAKSANAAN PRAKTIK PENGALAMAN LAPANGAN (PPL) II PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM DI MTsN 1 LANGKAT - Muhammad Riski, Syahputra; Khofifah Riana Br, Bangun; Khaira, Mufliha; Fitri, Aulia (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2025)
This study aims to evaluate the implementation of the Field Experience Practice (PPL) programme at MTsN 1 Langkat which focuses on developing student competence in the world of education, especially in madrasah. The research method used is qualitative evaluative with observation, interview, and document study approaches. The data was analysed through interactive analysis which includes collecting, simplifying, presenting data, and drawing conclusions. The results showed that MTsN 1 Langkat succeeded in integrating formal education with religious values and local traditions through various school culture programmes such as Clean Friday, dhikr together, and Islamic holiday commemoration activities. In addition, madrasah administration and management services at MTsN 1 Langkat have been running well, indicated by the existence of clear strategic documents and consistent implementation. Participative madrasah leadership and adequate classroom management also support a conducive learning atmosphere. This programme provides valuable experience for students in understanding the challenges and opportunities in the world of education in a madrasah environment